Reflection of sv waves in the elastic half-space. field equations for angles of incidence less than the critical one: Reflection of sv waves in the elastic half-space. field equations for angles of incidence less than the critical one - Xolmurodov, A. E.; Matanov, M. Ch.; Quzratov-, M. A. (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
Abstract. In this article relations that allow to study the movement of the elastic half-space caused by the full total angle of incidence of Rayleigh-type and sh, p, sv seismic waves are established and the phenomena related to the propagation of waves across the terrain, analyzing the properties of each event wave in two-dimensional problems is studied. Besides, their specific properties, determining the properties of the fields formed by different waves, their expressions governing scattering and generalization to fully general angles of incidence are discussed